Estimation of Mangrove Density of Segara Anakan, Central Java Province, Indonesia - . Ismail; . Sulistiono; Sigid Hariyadi; Hawis Madduppa (Research Aspects in Agriculture and Veterinary Science Vol. 6, 2022)
In the present study, vegetation index algorithm or NDVI is calculated to analyze the current condition of mangrove of Segara Anakan. Mangrove Segara Anakan has high economic values and supports coastal fisheries. However, the condition of Segara Anakan mangrove is currently degraded due to various land uses which are more concerned with economic objectives than with mangrove conservation, thus causing criticality of mangrove land. Mangrove density is one indicator of the critical level of mangrove land. The objective of this research was to analyze the density level of mangrove cover of Segara Anakan. The method used was Normalized Difference Vegetation Index (NDVI) based on the interpretation of satellite image of Landsat 8 acquisition by 4 April 2016, and this is classified based on Guidelines of Inventory and Identification of Critical Land of Mangrove of Forestry Department in 2005. The result of data processing of Landsat 8 image shows that mangrove crown density of Segara Anakan based on NDVI is divided into dense class (4,792.11 ha), medium class (762,11 ha) and sparse class (571,95 ha) with the total area of mangrove of 6,126.28 hectare. The strengthening of social capital in improving the understanding of the limits of capacity of mangrove ecosystems and estuary waters need to be improved through education and counseling on mangrove ecosystem and aquatic environment.